Valoración de la carga antigénica h, mediante la tipificación sanguínea directa, a muestras de sangre de pacientes de la unidad de medicina interna del hospital provincial general docente de riobamba que han sido administrados como alternativa transfusional paquetes globulares, en prevención de reacciones hemolíticas, durante el periodo diciembre 2014 a mayo 2015. - Pilco Vela, Jessica Viviana (2015)
This research work assessing the antigen H charge, through direct blood typing, a blood samples from patients in the Internal Medicine Unit of the Provincial General Teaching Hospital in Riobamba that have been administered as a transfusion alternative packed red blood cells, prevention haemolytic reactions, aims to rule out transfusion complications in administering packed red blood cells by applying the typing test blood directly as primary analysis in the patient sample and ensure blood transfusion with the use of Coombs, because they can in several people generate a production or increase the level or concentration of antibodies history of pregnancies or transfusions that might endanger the health when they receive blood or packed red blood cells containing a variety of antigens in different concentrations, to support the theoretical framework computer uses the information sources that support blood groups, techniques used for analysis and the characteristics of those derived from whole blood are obtained and made available to transfusion therapy.